Fracture toughness analysis of a ductile steel by means of 3D surface displacements - Paolinelli, Luciano Daniel (2013)
The standards for characterization of fracture toughness of metals are focused on the calculation of fracture parameters based only on in-plane displacements of the specimen tested. Although fracture is a three-dimensional problem, out-of-plane displacements of the specimen tested are not mentioned in those documents. Since three-dimensional displacement measurement is available, it is worth investigating its potential uses in fracture tests. In this work, the fracture toughness of a structural steel was assessed through standard tests, measuring three-dimensional surface displacements. An alternative Crack Tip Opening Displacement calculation was introduced. The fracture initiation was inferred from the out-of-plane displacements, finding good agreement with results from R-curves.